Perancangan Perbaikan Positioning Produk Kemeja Schouten Berdasarkan Perceptual Mapping dengan Metode Multidimensional Scaling - Hafizhah Khaerani; Yati Rohayati; Ima Normalia Kusumayanti (Journal of Management and Bussines (JOMB), 2023)
This study aims to identify the attributes of the shirt using perceptual mapping and the resulting map will be the basis for recommendations for improvements in the positioning of Schouten shirt products. Positioning is carried out using the Multidimensional scaling method which produces a Perceptual mapping from the results of the perceptions of 121 respondents who are shirt consumers on 11 attributes on each shirt brand. From the results of the Perceptual Mapping, we get the priority attributes of improvement and Schouten's closest competitor, Sipolos, based on Euclidean distance. In addition, based on the results of the Perceptual Mapping, a positioning improvement plan for Schouten shirt products was made with an integrated positioning system design for Schouten based on the shirt's attributes which are a unique value proposition to improve positioning and consumer perceptions of Schouten. There is an attribute of the Schouten shirt product which is a priority for improvement, namely the variety of models to improve consumer perceptions of Schouten and increase brand awareness of the Schouten brand. Keywords: Positioning, Multidimensional Scaling, Perceptual Mapping, Shirt Product, Schouten